Functional Improvement of Chimeric Antigen Receptor Through Intrinsic Interleukin-15Rα Signaling - Nair, Sushmita; Wang, Jing-Bo; Tsao, Shih-Ting; Liu, Yuchen; Zhu, Wei; Slayton, William B.; Moreb, Jan S.; Dong, Lujia; Chang, Lung-Ji (Current Gene Therapy, 2019)
Introduction: Recent studies on CD19-specific chimeric antigen receptor (CAR)-modified T cells (CARTs) have demonstrated unprecedented successes in treating refractory and relapsed B cell malignancies. The key to the latest CART therapy advances can be attributed to the improved costimulatory signals in the CAR design. Methods: Here, we established several novel CARs by incorporating T cell signaling domains of CD28 in conjunction with intracellular signaling motif of 4-1BB, CD27, OX40, ICOS, and IL-15Rα. These novel CARs were functionally assessed based on a simple target cell killing assay. Results: The results showed that the CD28/IL-15Rα co-signaling (153z) CAR demonstrated the fastest T cell expansion potential and cytotoxic activities. IL-15 is a key cytokine that mediates immune effector activities. The 153z CARTs maintained prolonged killing activities after repetitive rounds of target cell engagement. Consistent with the enhanced target killing function, the 153z CARTs produced increased amount of effector cytokines including IFN-γ, TNFα and IL-2 upon interaction with the target cells. Conclusion: In a follow-up clinical study, an acute lymphoblastic leukemia (ALL) patient, who experienced multiple relapses of central nervous system leukemia (CNSL) and failed all conventional therapies, was enrolled to receive the CD19-specific 153z CART treatment. The patient achieved complete remission after the 153z CART cell infusion. The translational outcome supports further investigation into the safety and enhanced therapeutic efficacy of the IL-15Rα-modified CART cells in cancer patients.
Keywords: acute B lymphoblastic leukemia